2010
DOI: 10.1017/s0022112010000170
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of particles in incompressible random flows: singularities, intermittency and random uncorrelated motion

Abstract: The results presented here are part of a long-term study in which we analyse the segregation of inertial particles in turbulent flows using the so called full Lagrangian method (FLM) to evaluate the ‘compressibility’ of the particle phase along a particle trajectory. In the present work, particles are advected by Stokes drag in a random flow field consisting of counter-rotating vortices and in a flow field composed of 200 random Fourier modes. Both flows are incompressible and, like turbulence, have structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 34 publications
4
54
0
1
Order By: Relevance
“…For inertial particles (i.e. finite Stokes number) the correlations in α A result from the preferential concentration of particles (see, e.g., Sundaram & Collins 1999;Ahmed & Elghobashi 2000), particle trajectory crossing (see, e.g., Simonin 1996;IJzermans et al 2010) and to particle clustering (see, e.g., Agrawal et al 2001).…”
Section: B2 Phase Averagementioning
confidence: 99%
See 1 more Smart Citation
“…For inertial particles (i.e. finite Stokes number) the correlations in α A result from the preferential concentration of particles (see, e.g., Sundaram & Collins 1999;Ahmed & Elghobashi 2000), particle trajectory crossing (see, e.g., Simonin 1996;IJzermans et al 2010) and to particle clustering (see, e.g., Agrawal et al 2001).…”
Section: B2 Phase Averagementioning
confidence: 99%
“…In the KT of granular flow, the velocity distribution represents the velocities present in an instantaneous flow field. In other words, at a given time and location in the flow, it is possible to find particles with different velocities (see, e.g., Février et al 2005;IJzermans et al 2010). In contrast, p.d.f.…”
Section: Introductionmentioning
confidence: 99%
“…This also enables one to calculate the particle concentration (the rate of change of which is proportional to the divergence of the particle velocity field) along a particle trajectory and in turn the statistical moments of the volume-averaged particle concentration. IJzermans et al (2009IJzermans et al ( , 2010 and Reeks (2010, 2011) report measurements of the moments at small St and St = O(1) in simple periodic flows, kinematic simulations (with a distribution of energy and length scales typical of real turbulent flows) and in DNS of homogeneous isotropic turbulence. For small St the moments grow exponentially and smoothly with time, consistent with the behaviour predicted by Balkovsky et al (2001).…”
Section: Droplet Clusteringmentioning
confidence: 99%
“…Dynamical systems theory has been applied to the motion of particles, first by Sommerer and Ott 15 and in turbulent flows by Bec 16 and Wilkinson et al 17 who showed that periods in time exist where particle trajectories may cross leading to particle collisions. Relaxing an assumption of Wilkinson et al, 17 that the typical correlation time of the carrier flow is small, Reeks and co-workers have deployed the full Lagrangian method (FLM) of Ostiptsov 18 first in synthetic flows 19 and recently in isotropic turbulence 20 to quantify non-uniformities and singularities in the spatial distribution of particles more generally. The advantage of FLM being that the analysis takes place on infinitesimally small scales and does not rely on defining a box size for counting purposes and that a small Stokes number limit is not implicit in the method.…”
Section: Introductionmentioning
confidence: 99%